ADDENDUM TO OVERLAND FLOW TO AND THROUGH A SEGMENT OF UNIFORM RESISTANCE - Hogarth W.L.; Parlange J.Y.; Rose C.W. (My University, 2003)
The St Venant equation is used to model the steady flow of water on a low slope through a grass buffer strip represented by beds of nails of various densities. The analytical solution is obtained both for flow upstream and within the buffer strip. Solution only requires the boundary conditions far upstream to be given and no curve fitting of parameters. The sensitivity of the solution to uncertainty in the measured boundary conditions and the effect of the theoretical resistive flow equation used are explored. Differences are observed between experimental observations and the theory but these are likely to be due to the presence of turbulent waves at the surface of the flow which are not part of the model.
Keywords: UNIFORM RESISTANCE; BUFFER STRIPS; STEADY FLOW